2014
DOI: 10.1002/rcm.7032
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced detection of the algal toxin PbTx‐2 in marine waters by atmospheric pressure chemical ionization mass spectrometry

Abstract: Positive mode APCI represents a significant improvement in detection and quantification of PbTx-2 by LC/MS allowing for smaller sample sizes compared to previous studies using (+) ESI. This in turn leads to higher throughput of samples during and after bloom events giving stakeholders detailed information on the fate of this potent marine toxin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
1
1
0
Order By: Relevance
“…The CV increases the number of charges available for the ionization and the SGT improves the desolvation of compound and removes noise. The results are in agreement with Yogi et al, [45] and Mead et al, [49] suggesting that the electrospray ionization of such polyethers with very low number of ionizable groups (i.e. acidic or basic functional groups) can be challenging and requires stronger conditions.…”
Section: Significance Of the Factorssupporting
confidence: 91%
“…The CV increases the number of charges available for the ionization and the SGT improves the desolvation of compound and removes noise. The results are in agreement with Yogi et al, [45] and Mead et al, [49] suggesting that the electrospray ionization of such polyethers with very low number of ionizable groups (i.e. acidic or basic functional groups) can be challenging and requires stronger conditions.…”
Section: Significance Of the Factorssupporting
confidence: 91%
“…Full scan LC–MS has also been described with a single quadrupole detector for the determination of BTXs in water, air and shellfish samples [ 13 ]. Other workers have reported that atmospheric pressure chemical ionization performed better than electrospray ionization in the LC–MS detection of the brevetoxin-2 in seawater [ 94 ]. The use of both LC–MS/MS and accurate mass measurement for the identification of toxin metabolite structures has been demonstrated [ 84 ], with other workers describing the use of selected reaction monitoring (SRM) LC–MS/MS analysis for a range of specific BTXs [ 78 , 85 ].…”
Section: Toxin Testing Methodsmentioning
confidence: 99%